Time limits of remedies for hidden defects under under Directive (EU) 2019/770 on contracts for the supply of digital content and digital services and Directive (EU) 2019/771 on contracts forthe sale of goods - Gsell, Beate; Araldi, Rodrigo (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This paper addresses the issue of time limits for the effective exercise of remedies for lack of conformity in consumer sales contracts and contracts for the supply of digital content and digital services under the new Directives 2019/770 and 2019/771. In particular, it examines the time limits applicable in case of hidden defects, which only become apparent after the delivery of the goods or the supply of the digital content. It also addresses the more complex situation where such hidden defects exist in the context of contracts providing for a continuous supply over a period of time. The purpose of this article is to assess both the appropriateness of the legislative approach adopted in each directive and the coherence between the two directives as to the legal framework applicable to such time limits.